Public Perception of the Role of Business Legal Regulations in Strengthening the Entrepreneurship and MSME Ecosystem in Blitar City - Widhiandono, Erwin; Anjarwati, Sulistyo; Akbar, Jihadul (Kirana Publisher (KNPub), 2025)
This study examines public perceptions of the role of business law regulations in strengthening the entrepreneurial ecosystem and MSMEs in Blitar City. The background to this study is the importance of MSMEs in the national economy and the state's efforts to create a conducive business climate through legal policies (e.g., Law No. 20/2008 on MSMEs, Law No. 11/2020 on Job Creation). The approach used is qualitative phenomenological, with data collection through in-depth interviews (15 informants: MSME actors, practitioners, local officials, academics), participatory observation in the field, and a study of relevant policy documentation. The findings show that the community views business law regulations as an important instrument for providing certainty and protection (e.g., business legality), but in practice, there are bureaucratic obstacles and a lack of socialization that hinder their effectiveness. The novelty of this research lies in the local context of Blitar City and the use of a phenomenological approach to explore the subjective meanings of the actors. Based on the findings, it is concluded that although regulations have the potential to support the empowerment of MSMEs and the regional economy (in line with Welfare State theory), implementation in the field needs to be strengthened by simplifying procedures, providing legal assistance, and strengthening law enforcement so that it does not become an obstacle for business actors.